The Influence of dietary lipid composition on skeletal muscle mitochondria from mice following eight months of calorie restriction - Chen, Yana (2013)
Calorie restriction (CR) has been shown to decrease reactive oxygen species (ROS) production and retard aging in a variety of species. It has been proposed that alterations in membrane saturation are central to these actions of CR. As a step towards testing this theory, mice were assigned to 4 dietary groups (control and 3 CR groups) and fed AIN-93G diets at 95% (control) or 60% (CR) of ad libitum for 8 months. To manipulate membrane composition, the primary dietary fats for the CR groups were soybean oil (also used in the control diet), fish oil or lard. Skeletal muscle mitochondrial lipid composition, proton leak, and H(2)O(2)production were measured. Phospholipid fatty acid composition in CR mice was altered in a manner that reflected the n-3 and n-6 fatty acid profiles of their respective dietary lipid sources. Dietary lipid composition did not alter proton leak kinetics between the CR groups. However, the capacity of mitochondrial complex III to produce ROS was decreased in the CR lard compared to the other CR groups. The results of this study indicate that dietary lipid composition can influence ROS production in muscle mitochondria of CR mice. It remains to be determined if lard or other dietary oils can maximize the CR-induced decreases in ROS production.